Student’s Sports, Mass Sports and High-Rise Sports - Allaniyazov Zakir (Sinar Sport Journal, 2024)
The article explores the role of mass sports within the framework of physical culture in a post-industrial society, distinguishing it from elite sports. Mass sports are characterised as accessible activities aimed at improving health, enhancing physical fitness, and fostering overall well-being among diverse populations. In contrast, elite sports focus on high performance and competitive success. The article discusses how mass sports align with the broader objectives of physical culture, emphasising their benefits for mental and emotional health. It highlights the importance of competition in mass sports, which differentiates them from general physical culture practices. Overall, the article underscores the significance of mass sports as a universal and relevant avenue for personal and communal engagement in physical activity, addressing the contemporary need to fulfil physical and psychological needs.